Adult learning for social change in museums: An exploration of sociocultural learning approaches to community engagement. Issue 2 (November 2016) - Kim, Junghwan; You, Jieun; Yeon Park, Soo
This integrative literature review critically examined how scholars were articulating the work of museums to make a space for 'adult learning for social change through community engagement'. We applied sociocultural adult learning theories (situated learning and cultural-historical activity theory), to 25 theoretical and empirical studies in predominantly museum and culture-based journals but also, specific adult education and lifelong learning journals. We found the studies shared in the works underscored the importance of social, collective interactions (adult learning for social change through community engagement) in the informal settings of museums and the work of various learning mediators of learning such as educators, tour guides and even, curators. In particular, we found a belief in the value of participatory collaborations based on community needs. However, when it came to practice, most studies illuminated passive, individualised processes of learning confined to pre-organised education activities. We argue therefore, that although museums have great potential to become meaningful spaces for adult learning for social change through community engagement, there is a disconnection between a belief/application of more critical, sociocultural learning perspectives and the actual practices under study. We argue that an application of what these theories suggest is needed to strengthen adult learning for social change through community engagement in museums.